Drivers of informal sector and non-prescription medication use in pediatric populations in a low- and middle-income setting: A prospective cohort study in Zambia. - Sanne Wildbret; Logan Stuck; Chaluma C Luchen; Michelo Simuyandi; Caroline Chisenga; Constance Schultsz; Vanessa C Harris (Public Library of Science (PLoS), 2023)
Obtaining medication from the informal sector is common in low- and middle- income countries. Informal sector use increases the risk for inappropriate medication use, including inappropriate antibiotic usage. Infants are at the highest risk of complications from inappropriate medication use, yet there is insufficient knowledge about the risk factors driving caregivers to obtain medication from the informal sector for young children. We aimed to define infant and illness characteristics associated with use of medication purchased in the informal sector for infants up to fifteen months of age in Zambia. We used data from, a prospective cohort study (ROTA-biotic) conducted among 6 weeks to 15 months old children in Zambia, which is nested within an ongoing phase III rotavirus vaccine trial (Clinicaltrial.gov NCT04010448). Weekly in-person surveys collected information about illness episodes and medication usage for the trial population and for a community control cohort. The primary outcome for this study was whether medication was purchased in the formal sector (hospital or clinic) or informal sector (pharmacy, street vendor, friend/relative/neighbor, or chemical shop) per illness episode. Descriptive analyses were used to describe the study population, and the independent and medication use variables stratified by the outcome. A mixed-effects logistic regression model with a participant-level random intercept was used to identify independent variables associated with the outcome. The analysis included 439 participants accounting for 1927 illness episodes over fourteen months in time. Medication was purchased in the informal sector for 386 (20.0%) illness episodes, and in the formal sector for 1541 (80.0%) illness episodes. Antibiotic usage was less common in the informal sector than in the formal sector (29.3% vs 56.2%, p < 0.001, chi-square). Most medications purchased in the informal sector were orally administered (93.4%), and non-prescribed (78.8%). Increased distance from the closest study site (OR: 1.09; 95% CI: 1.01, 1.17), being included in the community cohort site (OR: 3.18; 95% CI: 1.86, 5.46), illnesses with general malaise fever, or headache (OR: 2.62; 95% CI: 1.75, 3.93), and wound/skin disease (OR: 0.36; 95% CI: 0.18, 0.73) were associated with use of medication from the informal sector. Sex, socioeconomic status, and gastrointestinal disease were not associated with use of medication from the informal sector. Informal sector medication use is common and, in this study, risk factors for obtaining medications in the informal sector included a long distance to a formal clinic, type of illness, and not being enrolled in a clinical trial. Continued research on medication use from the informal sector is crucial and should include generalizable study populations, information on severity of disease, emphasis on qualitative research, and a move towards testing interventions that aim to improve access to formal health care settings. Our findings suggest that improved access to formal health care services may decrease reliance on medication from the informal sector for infants.